Influence of Walker Curve Tooth Root Modification on Thermoelastic Grease Lubrication Characteristics of Large Internal Gears - Wang Zhenbo; Zheng Peng; Zhao Wenhui (Jixie chuandong)
The influence of Walker curve modification method on the tooth surface lubrication state of grease lubricated large internal meshing cylindrical spur gears is studied. According to the meshing law and engineering experience of internal meshing gear pairs, the tooth profile between pinion base circle and pitch circle is determined as an example, the tooth profile curve after modification is parameterized, the calculation model of tooth surface oil film thickness is established, and the lubrication state of modified tooth profile is numerically analyzed. The results show that the modification theory and experience of the same kind of small gears cannot be fully used for reference in the modification of large gears. The linearly increased modification amount cannot make the lubrication state of the tooth surface change linearly. Increasing the viscosity of grease can effectively improve the local poor lubrication caused by the defect of the modification curve.